The Fabulous Saga of Guðmundr inn ríki. Representation of Sexuality in Ljósvetninga saga - Tirosh, Yoav, 1985- (2014)
Medieval Icelandic gender and sexuality have been a constant source of scholarly debate since the late 20th century, with Preben Meulengracht Sørensen and Carol J. Clover elucidating the volatile nature of Old Norse masculinity. Medieval explanations for sex difference have also been a source of much debate in this period, Thomas W. Laqueur’s controversial and popular one-sex model complemented by Joan Cadden’s more heterogeneous treatment of the issue. This thesis provides an extensive interpretation of Guðmundr inn ríki’s portrayal in Ljósvetninga saga. Guðmundr, a powerful goði living in the late 10th and early 11th century, was subjected to sexual insults by his rivals Þorkell hákr and Þórir goði Helgason. These sexual insults described him as effeminate and cowardly, and the thesis shows that the Ljósvetninga saga text follows suit with these slurs. Guðmundr’s description is tied with medieval medical perceptions of sex difference, and with gender perceptions prevalent in medieval Iceland. It is argued that these are not so distant as sometimes suggested, supported by Lars Lönnroth’s study of Latin scholarship’s influence on Íslendingasögur character descriptions. Keywords: argr, níð, homosexuality, sodomy, sex difference, gender, medieval sexuality, medieval medicine, medieval Iceland, Ljósvetninga saga, Guðmundr inn ríki Kyn og kynhneigð á Íslandi á miðöldum hafa verið mjög til umræðu meðal fræðimanna á seinustu áratugum frá því að meðal annars Preben Meulengracht Sørensen og Carol J. Clover drógu fram hið óvissa eðli fornnorrænnar karlmennsku. Hugmyndir miðaldamanna um kyn hafa verið mjög til umfjöllunar á þessu tímabili, einkum hið umdeilda en vinsæla „eins–kyns-líkan“ eftir Thomas W. Laqueur og rækilegri og vandaðri umfjöllun Joan Caddens um málið. Þessi ritgerð felur í sér rækilega túlkun á ímynd Guðmundar ríka í Ljósvetninga sögu. Guðmundur var öflugur goði sem var uppi undir lok 10. aldar og snemma á 11. öld og var níddur af keppinautum sínum, þeim Þorkatli háka og Þóri goða Helgasyni. Í níðinu ...